Microbial density and diversity in constructed wetland systems and the relation to pollutant removal efficiency - Zhang, Yang (Water science and technology : a journal of the International Association on Water Pollution Research, 2016)
Microbes are believed to be at the core of the wastewater treatment processes in constructed wetlands (CWs). The aim of this study was to assess the microbial biomass carbon (MBC) and Shannon's diversity index (SDI) in the substrate of CWs planted with Phragmites australis, Hymenocallis littoralis, Canna indica and Cyperus flabelliformis, and to relate MBC and SDI to the pollutant removal in the systems. Significant higher MBC was observed in CWs with H. littoralis and C. indica than in CWs with P. australis, and the MBC differed with season and substrate depth. The microbial community in the wetlands included four phyla: Cyanobacteria, Proteobacteria, Chloroflexi, and Acidobacteria, with a more diverse community structure in wetlands with C. flabelliformis. The MBC in the substrate and the SDI of the 15-20 cm depth correlated with the removal of biochemical oxygen demand, NH4-N and NO3-N. Our results indicate that substrate SDI and MBC can both be regarded as bioindicators of the pollutant removal ability in CWs